溶融Al-Si-Mg合金めっき鋼板のめっき組成と腐食挙動 - 真木, 純; 伊崎, 輝明; 山口, 伸一; 黒﨑, 将夫 (鉄と鋼, 2013)
This study was intended to investigate the effect of the amount of Mg and Si addition in the Al-Si coating in order to improve corrosion resistance of Aluminized steel sheets. A salt spray test using formed specimens proved that Al-8mass%Si-6mass%Mg-coated steel sheet having less cracks in the alloy layer after forming has the best corrosion resistance. This outdoor exposure test using unformed specimens for 10 years proved that corrosion weight loss of Al-8mass%Si-6mass%Mg-coated steel sheet was reduced to approximately 30% less than that of Aluminized steel sheets and approximately 70% less than that of 55% aluminum-zinc alloy-coated steel sheets; thereby, it was possible to confirm that Al-8mass%Si-6mass%Mg-coated steel sheet has favorable corrosion resistance under a long-term atmospheric environment. This is supported to be the protective effects caused by corrosion products mixed with Si and Mg, since the current value of the cathode polarization method of the specimen of Al-8mass%Si-6mass%Mg-coated steel sheet after the outdoor exposure test in an artificial rain solution were reduced by approximately 40% less than that of aluminized steel sheet.